Kinematic and muscle activity patterns of maximal ice hockey skating acceleration - Kaartinen, S.; Vartiainen, P.; Venojärvi, M.; Tikkanen, H.; Stenroth, L. (International Journal of Performance Analysis in Sport, 2026)
The ability to rapidly accelerate while skating is an essential quality for ice hockey players. Detailed neuromechanical characteristics of the performance should be known to inform strategies to improve skating acceleration capacity. In this study, we aimed to describe cycle-by-cycle lower limb kinematic and muscle activation patterns during a maximal effort 30 m ice hockey skating sprint. Twelve high-calibre players performed five maximal forward skating sprints. Muscle activities from eight lower limb muscles and sagittal plane joint kinematics from the hip and knee joints were measured throughout the sprint and reported cycle-by-cycle until the 7th cycle. The duration of the skating cycle and propulsion phase increased progressively from the 2nd until the 7th cycle. Qualitatively, the muscle activity patterns were quite similar between the cycles. However, some differences in the muscle activity levels during different cycle phases were identified in the accelerative cycles (cycles 1-6) compared to the maximal speed skating (7th cycle). The knee but not hip range of motion during the propulsion phase increased cycle-by-cycle, with the knee having a more flexed angle at the beginning of propulsion as the sprint progressed. The results can be used to inform training regimes to improve ice hockey skating acceleration.